Stochastic resonance in a metal-oxide memristive device. (March 2021) - Mikhaylov, A.N.; Guseinov, D.V.; Belov, A.I.; Korolev, D.S.; Shishmakova, V.A.; Koryazhkina, M.N.; Filatov, D.O.; Gorshkov, O.N.; Maldonado, D.; Alonso, F.J.; Roldán, J.B.; Krichigin, A.V.; et al.
Abstract: The stochastic resonance phenomenon has been studied experimentally and theoretically for a state-of-art metal-oxide memristive device based on yttria-stabilized zirconium dioxide and tantalum pentoxide, which exhibits bipolar filamentary resistive switching of anionic type. The effect of white Gaussian noise superimposed on the sub-threshold sinusoidal driving signal is analyzed through the time series statistics of the resistive switching parameters, the spectral response to a periodic perturbation and the signal-to-noise ratio at the output of the nonlinear system. The stabilized resistive switching and the increased memristance response are revealed in the observed regularities at an optimal noise intensity corresponding to the stochastic resonance phenomenon and interpreted using a stochastic memristor model taking into account an external noise source added to the control voltage. The obtained results clearly show that noise and fluctuations can play a constructive role in nonlinear memristive systems far from equilibrium.